المُهمّشون في الموروث الإباضي النوازلي: كتاب مسائل نفوسة الجبل للإمام عبد الوهاب بن عبد الرحمن بن رستم (171-208ه/787-823م) أنموذجاً.The marginalized in the Ibadi Nawazli heritage: The book “Masa’il Nafusa al-Jabal” by Imam Abd al-Wahhab ibn Abd al-Rahman ibn Rustum (171-208 AH/787-823 AD) as a model - حسين, نصر الدين; حسبلاوي, نسيم (المجلة التاريخية الجزائرية, 2024)
كتب النوازل الفقهية من أهمّ المصادر في الكتابة التاريخية، لما تختزنه من معلومات عن شرائح المجتمع المختلفة، فهي تحوي معلومات قيّمة عن الفئات المهمّشة كالفقراء؛ واللّصوص؛ والعبيد؛ وغيرها من الفئات التي طالها التّهميش، ولعلّ من أهم كتب النوازل التي ساهمت في إزالة الستار عن بعض هذه الشرائح في المجتمع الإباضي كتاب: "مسائل نفوسة الجبل"، للإمام عبد الوهاب بن عبد الرّحمن بن رستم، وانطلاقا من هذا الطّرح سنحاول في هذه الدّراسة معرفة أهمّ الفئات المُهمّشة التي تعرضت لها مسائل الكتاب والأوضاع التي كانت تعيشها دون تحميل النّص الفقهي ما يخرجه عن نطاق الدّراسة. Jurisprudential novels are among the most important sources of historical writing, as they contain information about different segments of society. They contain valuable information about marginalized groups such as the poor. And thieves; and slaves; And other groups that have been marginalized.Perhaps one of the most important books on disasters that helped to lift the curtain on some of these segments of Ibadi society is the book: "Questions of the Naffousa of the Mountain," by Imam Abd al-. Wahhab bin Abd al-Rahman bin Rustam. On the basis of this proposal, we will try in this study to discover the most important marginalized groups who were exposed to the issues of the book and the conditions in which they lived without weighing down the jurisprudential text. which takes him out of the field of study.
Keywords: Fiqh – Libye – 9e siècle